Current classification and diversity of Fusarium species complex, the causal pathogen of Fusarium wilt disease of banana in Malaysia - Ujat, Anysia Hedy; Vadamalai, Ganesan; Hattori, Yukako; Nakashima, Chiharu; Wong, Clement Kiing Fook; Zulperi, Dzarifah (Multidisciplinary Digital Publishing Institute, 2021)
The re-emergence of the Fusarium wilt caused by Fusarium odoratissimum (F. odoratissimum) causes global banana production loss. Thirty-eight isolates of Fusarium species (Fusarium spp.) were examined for morphological characteristics on different media, showing the typical Fusarium spp. The phylogenetic trees of Fusarium isolates were generated using the sequences of histone gene (H3) and translation elongation factor gene (TEF-1α). Specific primers were used to confirm the presence of F. odoratissimum. The phylogenetic trees showed the rich diversity of the genus Fusarium related to Fusarium wilt, which consists of F. odoratissimum, Fusarium grosmichelii, Fusarium sacchari, and an unknown species of the Fusarium oxysporum species complex. By using Foc-TR4 specific primers, 27 isolates were confirmed as F. odoratissimum. A pathogenicity test was conducted for 30 days on five different local cultivars including, Musa acuminata (AAA, AA) and Musa paradisiaca (AAB, ABB). Although foliar symptoms showed different severity of those disease progression, vascular symptoms of the inoculated plantlet showed that infection was uniformly severe. Therefore, it can be concluded that the Fusarium oxysporum species complex related to Fusarium wilt of banana in Malaysia is rich in diversity, and F. odoratissimum has pathogenicity to local banana cultivars in Malaysia regardless of the genotype of the banana plants.